Carbohydrase enzymes improve performance of broilers fed both nutritionally adequate and marginal wheat-based diets. (12th July 2017) - Wu, D.; Choct, M.; Wu, S. B.; Liu, Y. G.; Swick, R. A.
Summary: A study was conducted to examine the effects of a multi-carbohydrase enzyme complex on the nutritive value of wheat in diets differing in nutrient density. It was hypothesised that response to enzyme inclusion would be greater in diets with lower nutrient density. The study was conducted using 1008 Ross 308 male broiler chicks (four treatments with seven replicate pens of 36 chicks). A 2 × 2 factorial arrangement of treatments was employed. Factors were adequate or low nutrient density with or without enzyme supplementation. The wheat-soybean meal based positive control (PC) diet was formulated to be nutritionally adequate in energy and digestible amino acids according to local industry recommendations. A negative control (NC) was formulated to have 80 kcal/kg less ME and 1.5% less digestible amino acids as compared to the PC. A multi-carbohydrase complex containing 19 carbohydrase activities derived from Penicillium funiculosum was added in both the PC and NC diets (Rovabio ® Excel LC, Adisseo Asia Pacific Pte Ltd., Singapore). Birds fed the NC had 3.7 points (P < 0.05) poorer FCR than the PC. Across the diet type, enzyme supplementation increased body weight by 3.2% (P < 0.05) and improved FCR by 5.2 points (P < 0.01). There was no nutrient density x enzyme interaction (P > 0.05), indicating that performance improvement was independent of nutrient density. Apparent ileal digestibility of crude protein followed a similar trend, showing a 4.9% enhancement (P < 0.01) with the inclusion of the enzyme product in either diet. Enzyme supplementation reduced ileal viscosity by 39.0% (P < 0.05). It was concluded that multi-carbohydrase could overcome the negative effect in broiler performance brought by nutrient reduction, however, there was no indication that nutrient density affected bird response to supplementation of multi-carbohydrase.